The quality of life questionnaire EQ-5D-5L: psychometric properties and normative values for the general German population - Hinz, Andreas; Kohlmann, Thomas; Stöbel-Richter, Yve; Zenger, Markus; Brähler, Elmar (Quality of life research, 2014)
Purpose The health state classifier EQ-5D of the Euro-QoL group has been expanded to a 5-level instrument (EQ-5D-5L), but studies on psychometric properties of this new instrument, applied to the general population, are rare. Methods A sample of 2,469 subjects, representatively selected from the German general population, was asked to fill in the EQ-5D-5L and several other questionnaires. Crude sum scores of the EQ-5D-5L were calculated and compared with scores derived from two sets of utilities, one from a German and one from a UK sample. Results The mean sum score (0–100 scale) was 91.5. Males reported better health states than females, and there was a nearly linear age trend. The list of the 45 most frequent health patterns (those with at least 0.2 % of the respondents) showed that almost half of the participants (47.5 %) responded being in the optimal health state, indicating a ceiling effect. Correlations between EQ-5D-5L scores and other questionnaires were very similar for all three scoring systems of the EQ-5D-5L. Finally, normative scores are given on the basis of sum scores. Conclusions The applicability of the EQ-5D-5L in the general population is limited because of the skewness. Sum scores are useful because of their simplicity, international generalizability, and construct validity.